The invisible threat: A 30-year review of air pollution's impact on diarrhoea from the global burden of disease study 2021 - Changhao Zhang; Kaiqi Yang; Yang Yu; Haoxi Liu; Yijun Chen; Jiaxuan Zuo; Minyue Yin; Yuchen Ding; Jinlong Chen; Xiujing Sun; Shutian Zhang (Ecotoxicology and Environmental Safety)
Background: Diarrhoea remains a major contributor to global morbidity and mortality among children younger than 5 years. This study aims to provide an updated assessment of diarrhoea deaths and disability-adjusted life years (DALYs) attributable to air pollution from 1990 to 2021. Methods: The deaths and DALYs data for diarrhoea attributable to air pollution were derived from the 2021 Global Burden of Diseases Study (GBD). Age-standardized rates (ASRs) and estimated annual percentage changes (EAPCs) were used to assess trends in deaths related to diarrhoea. In addition, Auto-Regressive Integrated Moving Average (ARIMA) and Ensemble Smoothing (ES) models were used to predict the epidemic trends of diarrhoea from 2022 to 2046, and frontier analysis was conducted to explore the potential reduction in the burden of diarrhoea in different regions. Results: Globally, from 1990 to 2021, there were 45,851 deaths from diarrhoea attributable to air pollution (95 % uncertainty interval [UI], 32,228–56,815) in 1990, and 6559 deaths (95 % UI, 4931 to 9245) in 2021. In total, diarrhoea attributable to air pollution was responsible for 4134,309 DALYs (95 % UI, 1073,440 to 1277,490) in 1990, and 593,960 DALYs (95 % UI, 446,774 to 835,347) in 2021. The decreasing trend of diarrhoea burden is uneven in different countries and regions, with higher diarrhoea deaths and DALYs in low and low-middle SDI regions, while relatively lower in high SDI regions. Predictive analysis suggests that by 2046, deaths and DALYs of air pollution-related diarrhoea, as well as their corresponding ASR, will continue to decrease. Conclusion: Although the global burden of diarrhoea caused by air pollution has decreased in the past 30 years, it remains an important public health issue in low and low-middle SDI regions. The research findings emphasize the importance of public health policies and planning in reducing deaths related to diarrhoea and the disease burden, and point out the need for more targeted prevention strategies in order to reduce the disease burden.